Translating Digital Literature: Two Experiences and a Reflection - Giovanna di Rosario; Laura Borràs (Texto Digital)
In this article we would like to talk about our experience in translating digital poetry. In a text there are always elements that seem to be/are untranslatable. There will always be a certain degree of loss in meaning when a text is translated, but what does it mean to translate Electronic Literature? Electronic Literature is a transnational (thus translingual), interdisciplinary, and multimodal practice.  Electronic literature creates a text which is unstable; a text that can change its form and its content. The electronic text is causing a true reconfiguration of the literary creation, how can/should we translate a text that is unstable by its nature, that moves, changes and interacts with other semiotic systems? Though we are still at the beginning of this new discipline, nowadays, there are some examples of translation of e-literature: for instance the Finnish website nokturno.org provides translations into several languages of electronic literature. But what do we need to translate, to transfer into another language and into another culture, when we are translating electronic literature? What happens, for instance, to the aesthetic effects created by moving letters and their meaning when these words are translated to another languages whose structure could be very different from the departing language. How does one describe the intralingual and the intersemiotic translation process in e-literature? And how are different semiotic systems related to each other in an intersemiotic translation?